Teks-Teks Klasik Yoga dan Refleksinya bagi Pengajaran Yoga di Bali - Ni Kadek Surpi (Jurnal Yoga dan Kesehatan, 2021)
The long history of yoga has given birth to a number of important texts that became the source of learning Yoga, at a certain time. Yoga, whose origins are derived from the Rigveda, is a mindful practice of living in which physical and mental training has evolved to become the dominant physical training method in the modern age. A number of classical yoga texts such as Yoga Vasista, Yoga Sutras Patañjali, Goraksasatakam, Gheranda Samhita, Siva Samhita and Hatha Yoga Pradipika have influenced the knowledge and practice of yoga in Bali from the fourth to sixth centuries, before yoga's popularity continued to decline during the colonial period. Yoga is not a new product that has entered the modern era, after the formation of the Unitary State of the Republic of Indonesia, but Bali has become a conservationist for the world's yoga baboons. The ancient yoga training center is located on Mount Watukaru, so the yoga tradition is called Ancient Balinese Yoga, the Watukaru Tradition. Although there is no specific mention of the name of the text, a number of the same terminology at the relatively the same era is evidence that the influence of classical yoga texts has reached Bali at that time.